Implementation of Generative Artificial Intelligence (AI) in Learning: Analysis of Teachers' Pedagogical Readiness and Impact on Student Learning Autonomy in Indonesia - Moh, Solehuddin; Bahmid Hasbullah; Ai Siti Nurmiati; Syaharuddin; Muhammad Arsyad (International Journal of Educational Research Excellence (IJERE), 2025)
This quantitative study examined the implementation of Generative Artificial Intelligence (AI) in Indonesian educational settings, focusing on teachers' pedagogical readiness and its impact on student learning autonomy. A cross-sectional survey design involving 384 teachers from various educational institutions across Indonesia was employed. Data were collected using validated instruments measuring AI-TPACK (Technological Pedagogical Content Knowledge) competency and student learning autonomy. Results revealed that teachers demonstrated moderate levels of AI integration readiness (M = 3.29, SD = 0.95), with significant variations based on teaching experience and geographic location. Multiple regression analysis indicated that AI-TPACK integration was the strongest predictor of student learning autonomy (β = 0.425, p < 0.001), explaining 61.2% of the variance. Key challenges included infrastructure limitations (75.3%), lack of training (69.5%), and limited technical support (63.8%). The study concludes that successful AI implementation requires comprehensive teacher development programs, improved digital infrastructure, and systematic institutional support. Findings contribute to understanding AI integration dynamics in developing educational contexts and provide evidence for policy development in Indonesian education transformation.